The Determinants and Consequences of Child Care Subsidies for Single Mothers - David M. Blau; Erdal Tekin (Institute for the Study of Labor (IZA), 2001)
This paper provides an early analysis of child care subsidies under welfare reform. Previous studies of child care subsidies use data from the pre-welfare-reform period, and their results may not apply to the very different post-reform environment. We use data from the 1997 National Survey of America?s Families to analyze the determinants of receipt of a child care subsidy and the effects of subsidy receipt on employment, school attendance, job search, and welfare participation. We analyze the impact on subsidy receipt of household characteristics such as family size and structure, and past participation in welfare. Ordinary least squares estimates show positive and significant effects of subsidy receipt on employment, school enrollment, and welfare participation. Two stage least squares estimates that treat subsidy receipt as endogenous and use county dummies as identifying instruments show much less evidence that subsidy receipt affects these outcomes.
Keywords: J13; I38; 330; Welfare reform; child care subsidy; employment; Familienleistungsausgleich; Mütter; Alleinerziehende; Arbeitsangebot; Sozialhilfeempfänger; Schätzung; USA